Has China’s Health Sector Development Matched the Rapid Growth in the Country? - Tripane, Marta (European Scientific Journal, ESJ, 2017)
China is the world’s largest country by population, the third largest by territory and the second largest worldâ€™s economy by GDP. Therefore it is important to follow the successes and failures of China in the field of health, because they affect the health area and processes in the world. This article includes retrospective analysis of empirical data to analyze the main inputs and outputs of China’s health policy in order to identify the main problems and highlight the major challenges. In the article is concluded that main problems are related with insufficient and unequal access to health care.